Achievement Operation Performance: The Role of Soft TQM to Business Performance - Djolin, Kevin Nathanael Saputra; Sutrisno, Timotius F C W; Andrina, Anak Agung Ayu Puty (SAFE-Network, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving Indonesia’s economic growth, innovation, and job creation. However, the majority of MSMEs, particularly in the food and beverage sector, face significant challenges in quality control and operational efficiency due to limited internal resources. This study aims to investigate the effect of Soft Total Quality Management (Soft TQM) on Operational Performance and Business Performance, with Operational Performance examined as a mediating variable. Using a quantitative approach, data were collected through an online questionnaire distributed to 185 student-owned food and beverage businesses at Ciputra University Surabaya. Respondents were selected from three cohorts (2021, 2022, 2023) using a purposive sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results indicate that Soft TQM significantly affects Operational Performance, and that Operational Performance significantly affects Business Performance. However, the direct effect of Soft TQM on Business Performance, as well as its indirect effect through Operational Performance, is not statistically significant. These findings suggest that while Soft TQM can enhance internal operations, its impact on overall business performance is contingent upon the presence of structured systems and readiness of internal capabilities. Therefore, strengthening operational systems and aligning TQM practices with organizational strategy is crucial for MSMEs aiming for sustainable competitiveness.